Enhancing Healthcare Service Quality through Integrated Islamic Excellence Training: A Digital and Non-Digital Communication Approach - Pipit Wiliyanarti; Nanang Riono Wahyudi; Wison Pramu Asmiko; Herlin Ferliana (Health and Technology Journal (HTechJ), 2026)
Healthcare service quality relies heavily on effective communication and empathetic behavior alongside fundamental clinical competence. Islamic hospitals encounter unique challenges in integrating spiritual values into both face-to-face and digital patient interactions. This study aimed to enhance service excellence through an Integrated Islamic Service Excellence training program that addresses both digital and non-digital communication. Researchers utilized an adult learning framework with a pre-test and post-test evaluative design involving thirty frontline hospital personnel. The comprehensive intervention incorporated interactive lectures, simulation-based mentoring, and structured role-playing exercises. Training content seamlessly integrated standard 6S principles, core Islamic ethics, and Javanese local wisdom encapsulated by the Responsive, Respected, Treat, Spirit, and Embrace concepts. Quantitative evaluations revealed substantial improvements in participants' knowledge and professional attitudes following the intensive educational program. Mean post-test scores showed significant increases in service communication, patient empathy, and ethical conduct across both virtual and physical interactions. Observational data from practical simulations confirmed enhanced consistency in applying standardized service protocols during direct patient care. Participants demonstrated a marked ability to translate theoretical concepts into actionable workplace behaviors. The integrated training model effectively elevates healthcare personnel's competencies and fosters a deeply patient-centered service culture. This innovative framework offers a sustainable, replicable strategy for optimizing service quality across diverse Islamic and secular healthcare facilities globally.